1992
DOI: 10.1016/0735-1097(92)90495-9
|View full text |Cite
|
Sign up to set email alerts
|

Lung perfusion scans in patients with congenital heart defects

Abstract: In 63 patients with various congenital heart defects, lung perfusion was evaluated with technetium-99mm macroaggregated albumin. Right lung perfusion abnormalities were documented in 34 patients (54%). A particularly high incidence occurred in patients who had undergone a systemic to pulmonary artery shunt operation as an initial palliative procedure or who had had right ventricular outflow reconstruction and in those with bilateral pulmonary artery stenosis. Serial studies were helpful in evaluating the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…Phase-contrast flow measurement has been integrated in comprehensive cardiopulmonary MRI in evaluation of TOF (6,10). From In TOF after repair, it is important to know the differential lung perfusion, because asymmetry of lung perfusion is one of the predictors of outcome and exercise capacity (11)(12)(13)(14). Although the impact of pulmonary regurgitation on right ventricular dysfunction has been extensively investigated, its impact on lung perfusion has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase-contrast flow measurement has been integrated in comprehensive cardiopulmonary MRI in evaluation of TOF (6,10). From In TOF after repair, it is important to know the differential lung perfusion, because asymmetry of lung perfusion is one of the predictors of outcome and exercise capacity (11)(12)(13)(14). Although the impact of pulmonary regurgitation on right ventricular dysfunction has been extensively investigated, its impact on lung perfusion has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical impact. Precise estimation of pulmonary perfusion has gained an increasingly important role in comprehensive evaluation of cardiopulmonary function in TOF after repair (11)(12)(13)(14). Because peripheral pulmonary stenosis occurs not uncommonly over the LPA in repaired TOF, underestimation of differential perfusion of the left lung by conventional PC-MRI method with NFV ratio, as illustrated in Figure 1, would lead to an overestimation of LPA stenosis; as a result, unnecessary invasive procedures such as catheterization and balloon vascular dilatation might be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in adults have shown that the normal distribution in adult population with no cardiac anomalies is 52.5/47.5 (AE2.1%) for right/left lungs [6]. Nonetheless, some studies in children with congenital heart disease found normal blood flow distribution to both lungs in patent ductus arteriosus, although preferential flow to one lung or the other was significant in other defects such as pulmonary stenosis or ventricular septal defects [30][31][32]. Others have reported that some patients with PDA have an inherently preferential blood flow from the right ventricle to right pulmonary artery [33].…”
Section: Discussionmentioning
confidence: 95%
“…5). 15,16 Ventilation-perfusion scintigraphy Ventilation-perfusion scintigraphy (V/Q) is performed in children with suspected pulmonary thromboembolism, usually in the setting of contraindications to CT angiography, such as contrast allergy or renal disease, or when there are radiation concerns. 17 In repaired congenital diaphragmatic hernia, V/Q scintigraphy is useful to assess ventilation and perfusion abnormalities (Fig.…”
Section: Pulmonary Indications and Applicationsmentioning
confidence: 99%